Density and Survival of Walleye Eggs and Larvae in a Great Lakes Tributary. Issue 3 (19th April 2016) - Rutherford, E. S.; Allison, J.; Ruetz, C. R.; Elliott, J. R.; Nohner, J. K.; DuFour, M. R.; O'Neal, R. P.; Jude, D. J.; Hensler, S. R.
Abstract: The Walleye Sander vitreus is an important sport fish that has experienced low reproductive success in some Great Lakes tributaries since severe population declines began in the late 1940s. In the Muskegon River, a Lake Michigan tributary, natural reproduction of Walleyes remains low and is largely supplemented by stocking. We evaluated the influence of abiotic factors on Walleye reproductive success in the Muskegon River during April and May 2009 and 2010 by (1) estimating Walleye egg density and survival; (2) estimating the size, density, abundance, and survival of Walleye larvae; and (3) relating our estimates to physical habitat conditions. Egg densities were 70‐fold higher in 2009 than in 2010, but eggs experienced colder water temperatures, higher river discharge rates, and lower survival in 2009 relative to 2010. Egg survival in incubators was positively related to temperature and negatively related to flow at most sites. In both years, Walleye larvae that hatched during periods of cooler temperature were smaller than larvae that hatched later during periods of warmer temperature. Walleye larval densities were highest near spawning grounds and decreased downstream. Bayesian estimates of variability in larval densities indicated that temporal variability was twice as high as spatial variability in the Muskegon River. Larval survival was much lower in 2009 than in 2010, resulting in an approximately sevenfold higher production of larvae in 2010 than in 2009. Survival was highest for smaller larvae that hatched early in April 2010, when temperatures were warm and discharges were low and stable; in contrast, survival was much lower for larger larvae hatching later in 2010 or for large and small larvae in 2009, when water temperatures were colder and discharges were higher and more variable. Our results suggest that abiotic factors, primarily temperature and river flow, likely control the early survival of Walleyes in the Muskegon River. Received February 9, 2015; accepted January 11, 2016 Published online April 19, 2016